2011
DOI: 10.1242/jcs.084699
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion ofCyp26b1negatively impacts limb skeletogenesis by inhibiting chondrogenesis

Abstract: SummaryCyp26b1, a retinoic acid (RA)-metabolising enzyme, is expressed in the developing limb bud, and Cyp26b1 -/-mice present with severe limb defects. These malformations might be attributable to an RA-induced patterning defect; however, recent reports suggest that RA is dispensable for limb patterning. In this study, we examined the role of endogenous retinoid signalling in skeletogenesis using Cyp26b1 -/-mice and transgenic mice in which Cyp26b1 is conditionally deleted under control of the Prrx1 promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…Histologic analysis of phenotype for Cyp26b1 rec/rec embryos demonstrated abnormal limbs, epidermis, and whole mount photographs demonstrated a cleft of the secondary palate (Fig. 3) as have been described previously for these mutants [7,12,13]. Hematoxylin and eosin staining at E13.5 of Pitx2 rec/rec mutants showed incomplete closure of the abdominal wall with ectopic viscera including the lungs, heart, and intestine as has been reported previously for these mutants [14].…”
Section: Resultssupporting
confidence: 68%
“…Histologic analysis of phenotype for Cyp26b1 rec/rec embryos demonstrated abnormal limbs, epidermis, and whole mount photographs demonstrated a cleft of the secondary palate (Fig. 3) as have been described previously for these mutants [7,12,13]. Hematoxylin and eosin staining at E13.5 of Pitx2 rec/rec mutants showed incomplete closure of the abdominal wall with ectopic viscera including the lungs, heart, and intestine as has been reported previously for these mutants [14].…”
Section: Resultssupporting
confidence: 68%
“…However, forelimbs and hindlimbs are truncated along the entire proximodistal axis, which is inconsistent with RA functioning as an inducer of proximal identity. Further studies revealed that teratogenic mechanisms, such as increased apoptosis and a block in chondrogenic differentiation, cause the limb defects seen in Cyp26b1 −/− mice, overshadowing the effects of disrupted patterning of molecular markers 60,62,63 . Cyp26b1 −/− Rarg −/− double-mutant embryos display a partial rescue of Cyp26b1 −/− limb truncations, indicating that RARγ is important for RA-induced teratogenicity 62 .…”
Section: Ra Function During Limb Developmentmentioning
confidence: 99%
“…The genetic deletion of any single member of the RAR family ( RARα , RARβ , RARγ ) in mice results in a minor phenotype, while deletions of multiple RAR receptors (e.g. RARα/γ or RARβ/γ ) results in perinatal lethality with severe skeletal abnormalities [95] [96]. While most RAR and RXR genes are functionally redundant, RXRα -deficient mice die in utero [94].…”
Section: Retinoic Acid Signalingmentioning
confidence: 99%